The Phenomenon of Health Cadre Performance Motivation in Communities in The Homeland of The Baduy - Tatiana Siregar; Ritanti Ritanti; Indah Permatasari (Jurnal Keperawatan Silampari, 2024)
ABSTRACTThis study explores the phenomena that motivate Baduy Health Cadres to carry out their societal roles. This study uses a qualitative method of the Transcendental Phenomenology type. The results of the survey obtained seven main themes, namely: Increasing knowledge, Concern for residents, Self-actualization, Support for residents to have MCK, Cultural preservation, Compensation, and Cadre Training. In conclusion, the seven themes motivate Health Cadres to carry out their roles. Keywords: Self-Actualization, Health Cadres, Motivation, Compensation, Baduy Tribe